Effect of Good Corporate Governance and Gender Diversity on Earnings Management in Indonesia - Yopie, Santi; Chandrawati, Meliesa (Accounting Department, Faculty of Business and Management, Universitas Internasional Batam, 2023)
Purpose - The goal of this study is to ascertain the major impact of gender diversity and good corporate governance on earnings management. Research Method - In this study, sampling was done using a purposive sampling technique. Findings - The results of hypothesis testing show that the variables of independent commissioners have a negative effect on earnings management. Implication - The research sample can be expanded by adding various sectors, adding independent variables that can better explain earnings management.